2014
DOI: 10.1016/j.rser.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroxylation of serpentine minerals: Implications for mineral carbonation

Abstract: This review examines studies on the dehydroxylation of serpentine minerals published in the open literature from 1945 to 2013, with brief description of earlier work.Presently, the energy cost and technological complications, required to amorphise serpentine minerals by dehydroxylation, prevent their large-scale application for sequestering of CO 2 . The focus of the review is on thermal dehydroxylation, although mechanical dehydroxylation by grinding and shock, as well as thermomechanical dehydroxylation are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 53 publications
3
58
0
1
Order By: Relevance
“…This band could be linked to (Fe,Mg) 3 ‐OH liaisons of Fe‐rich trioctahedral chlorite (King & Clark, ). Note that this XRD and NIR behavior could not be attributed to serpentine (while the XRD peak position could correspond to serpentine) because its dehydration temperature is at 600°C (Dlugogorski & Balucan, ). Therefore, from the XRD behavior and the NIR analysis, this clay mineral is a Fe‐rich chlorite/smectite MLM with a low amount of smectite layers.…”
Section: Resultsmentioning
confidence: 99%
“…This band could be linked to (Fe,Mg) 3 ‐OH liaisons of Fe‐rich trioctahedral chlorite (King & Clark, ). Note that this XRD and NIR behavior could not be attributed to serpentine (while the XRD peak position could correspond to serpentine) because its dehydration temperature is at 600°C (Dlugogorski & Balucan, ). Therefore, from the XRD behavior and the NIR analysis, this clay mineral is a Fe‐rich chlorite/smectite MLM with a low amount of smectite layers.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that MA caused this peak to shift to a lower temperature region. The exothermic peak at 830 • C corresponds to crystallisation of forsterite and/or enstatite [7,11,12]. Its position did not change with increased milling time.…”
Section: Thermal Analysismentioning
confidence: 95%
“…This is mainly due to the fact that achieving the desired binding properties requires the calcination of large 2 of 14 volumes of raw materials within a narrow temperature range (depending on serpentinite composition), with strictly fixed residence. Recently, the increased reactivity of dehydroxylated serpentine minerals has been extensively studied with respect to their aqueous dissolution and carbonation (reviewed in [7,8]). This research has been driven by current interests in the extraction of metals from serpentine, and the reduction of anthropogenic CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemically bound water in serpentine structure may also has an influence in increase of chemical reactivity (Lackner et al, 1995). Dehydroxilation of serpentine may take place at the temperature above 550 o C, leading to produce amorphous material (Dlugogorski and Balucan, 2014).…”
Section: Implication To Carbon Dioxide Sequestrationmentioning
confidence: 99%